Feeding and other management Practices of Pulikulam cattle rearers in its native tract - Srinivasan, G (Indian Journal of Dairy Science, 2021)
Pulikulam cattle are native cattle breed of southern Tamil Nadu reared by the nomadic herd rearers and bull rearers. A field study was conducted to collect information on existing management practices followed by the Pulikulam cattle rearers at Pulikulam cattle breeding tract during November, 2020. A total of 60 nomadic rearers and 60 Pulikulam bull rearers were randomly selected from the breeding tract. Nomadic rearers practising grazing only, 70% of them migrate for grazing throughout the breeding tract. Grazing at hilly area was practised by 16.67 percent respondents and 13.33 percent respondents grazed at common pasture land. Sale of manure and male calves were the main source of income for the nomadic cattle rearers. Milking was practiced only in the morning time by the nomadic rearers in the Sivaganga district. Concentrate feed or mineral mixture feeding was not practised by the nomadic Pulikulam cattle rearers. It is concluded that no scientific management practices especially feeding management is in practice.Â Adoption of balanced feeding and supplementation with mineral mixture could improve the performance of this breed of cattle.